Severe rhabdomyolysis induced by co-administration of cocaine and heroin in a 45 years old man treated with rosuvastatin: a case report: Rhabdomyolysis induced by cocaine and heroin in a rosuvastatin user - Mitaritonno, Michele; Lupo, Mariarosaria; Greco, Ivana; Mazza, Angela; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2021)
The term rhabdomyolysis describes a damage involving striated muscle cells or fibers, often complicated by acute kidney injury. This syndrome can have different causes, but it is generally divided into two main categories: traumatic and non-traumatic rhabdomyolysis. Among medical causes, drugs and abuse substances play a pivotal role, being opioids, alcohol, cocaine and other substances of abuse. Among drugs, the case of statins is certainly the best known. Here we describe a paradigmatic case of a man treated with success and good tolerance for years with rosuvastatin, who developed a severe rhabdomyolysis complicated by AKI needing hemodialysis, after the assumption of two substances of abuse (cocaine and heroin). Emergency physicians need to be aware of this syndrome, since it must be clinically suspected in order to ask the Laboratory for appropriate tests. Given that troponins are now widely accepted as the unique biochemical “gold standard” for diagnosing acute coronary syndromes, CK and myoglobin (the “gold standard” tests for diagnosing rhabdomyolysis) have been erased from admission test panels of the vast majority of emergency departments.